THE RESULTS OF VARIETY TRIALS OF NEW VARIETIES OF MELONS IN CONDITIONS OF THE VOLGOGRAD TRANS-VOLGA REGION - E. A. Varivoda; M. S. Kornilova; G. V. Varivoda (Овощи России, 2018)
Presents comparative characteristics of the 4 new varieties of melon breeding Bykovskaya melon experiment station in comparison with the standard. A brief description and varietal characteristics of the new varieties of melons of different ripening periods. Data on the yield, length of vegetation period, dry matter content, as well as complex resistance to diseases. According to the results of comparative evaluation in station variety testing, new melon varieties exceed the standard in yield from 2.7 t/ha (Harmony) to 4.6 t/ha (Originalnaya x Osen), in dry matter content from 0.2% Cometa variety to 1.1% Harmony variety (standard Osen variety – 13.0%). Testing for complex resistance to Anthracnose and powdery mildew revealed that the lowest degree of damage in a hybrid combination of the Originalnaya x Osen was powdery mildew – 51.3%, with a score of 1.4, anthracnose – 80.6% at a score of 1.5.